Evaluation of global ocean tide models based on tidal gravity observations in China - Hongbo Tan (KeAi Communications Co., Ltd., 2021)
Previous studies show that the calculated loading effects from global ocean tide models do not match actual measurements of gravity attraction and loading effects in Southeast Asia. In this paper, taking advantage of a unique network of gravity tidal stations all over the Chinese mainland, we compare the observed and modeled tidal loading effects on the basis of the most recent global ocean tide models. The results show that the average efficiencies of the ocean tidal loading correction for O1, K1, M2 are 77%, 73% and 59%, respectively. The loading correction efficiencies using recent ocean tidal models are better than the 40 years old Schwiderskis model at coastal stations, but relative worse at stations far from ocean.